Socio-Political Representation of Muslim Women: The Case of Palestinian Murabitat at Al-Aqsa Mosque - Reem Adib Lulu; Taha Ibrahim Shabeeb; Luwaytha Salah Habeeb; Sohayle M Hadji Abdul Racman; Laythaldin Salah Habeeb (Journal of Islamic Thought and Civilization, 2024)
The current study aims to explore Palestinian Murabitat’s roles in protecting the Al-Aqsa Mosque. Thus, this research highlights several activities organised by Palestinian women at Al-Aqsa, focusing particularly on two prominent Murabitat figures in Al-Aqsa: Hanadi Halawani and Fatimah Khedr. The study also highlighted how Murabitat contributed to Muslim women’s empowerment in Palestine. Secondary sources, including newspaper articles and journal publications, provided the data for this study. The researchers analyzed the data using qualitative methods. The study revealed that the notion of old Ribat extended to include various forms and activities that achieve the main purpose of Ribat, which is to maintain a standing guard to defend the country. These activities include educational initiatives, prayers in Al-Aqsa Mosque, coordinating visits to all martyrs’ mothers, visiting the owners of demolished homes to assist and console them, taking part in solidarity protests with detainees and martyrs’ families, participating in demonstrations against illegal attacks on Al-Aqsa Mosque, protesting through cuisine, and preserving heritage to depict Palestinian resistance. The researchers contended that Palestinian women exemplify the resilience of Muslim women through their liberation from occupation and their courage to face threats and abuses. Hence, this research reinterprets the notion of the traditional Ribat from a contemporary perspective, while also contributing to the present literature on Muslim women’s socio-cultural contributions to their cultures. This Muslim women representation contradicts the prevalent Western stereotype and negative portrayal of Muslim women around the world.